CFD simulations for surf-riding occurrence assessment. (15th December 2020) - Begovic, E.; Gatin, I.; Jasak, H.; Rinauro, B.
Abstract: Surf-riding phenomenon occurs when a ship sailing in following waves is accelerated to wave celerity. In this paper, surf-riding occurrence is studied for the parent hull of the Systematic Series D by 3 degrees of freedom (DOF) CFD simulations. Simulation cases are chosen following IMO recommendations for a wavelength to ship length range and following IMO criterion for ship speed cases. Initial conditions for simulations are obtained from 1-DOF surge motion equation solved by bifurcation analysis. The aim is to define surf-riding limits for ship operability with a less conservative approach, taking into account force changes in waves compared to the one used in the 1-DOF model, which considers calm water approximations. After defining surf-riding boundaries in terms of wave heights for different wavelengths and ship speeds, calculated forces are analysed to evaluate the magnitude and trend of non-linear effects due to wave elevation and ship-wave interaction. A detailed analysis is conducted on resistance, thrust, and wave forces in surging and surf-riding conditions, comparing the applied methodologies. The introduction of wave velocity field influence in the thrust force and the calculation of Froude-Krylov wave-force up to actual wave profile have been discussed and identified as possible improvements of 1-DOF approach. Highlights: CFD simulations are performed for ship sailing in following waves. Surf-riding boundaries for different wave heights and lengths and ship speeds are reported. Forces obtained by 3-DOF CFD and 1-DOF surge model are analysed and compared. Application is shown for D Series parent hull in full scale. Difference in two methods are analysed and further improvements are discussed.